A paramagnetic monatomic photo-Fenton catalyst, a preparation method and application thereof

CN122875291APending Publication Date: 2026-10-09GUIZHOU MATERIAL IND TECH INSTITUE
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610854813.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-13
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

[0005]本发明提供一种顺磁单原子光自芬顿催化剂及其制备方法和应用,旨在解决现有芬顿和光芬顿技术中需要外加H2O2、Fe2+易流失、pH适用范围窄、H2O2生成与活化缺乏协同性、催化剂难以回收等技术难题,实现高效、经济、环境友好的有机污染物降解

Benefits of technology

(1)顺磁性延长电荷寿命:利用二茂铁的供电子特性与RF树脂的π电子体系构建电子自旋通道,产生顺磁性微环境,微扰近邻酚羟基,降低质子解离能垒,促进电子~质子耦合转移,同时利用钯对d轨道与O的p轨道的结合,加速H+的解离,提高O2双电子还原生成H2O2的效率;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122875291A_ABST
    Figure CN122875291A_ABST
Patent Text Reader

Abstract

The application provides a paramagnetic monatomic light self-Fenton catalyst, a preparation method and application thereof, and belongs to the technical field of photocatalysis. The preparation method comprises the following steps: dispersing a ferrocene derivative in an ethanol / water mixed solvent, then adding resorcinol to perform pre-polymerization, subsequently adding a formaldehyde solution, stirring uniformly, and obtaining a precursor solution; transferring the precursor solution into a high-pressure reaction kettle to perform a solvothermal polycondensation reaction, cooling to room temperature after the reaction is completed, filtering and collecting a solid product, and obtaining a ferrocene modified phenolic resin (RF~Fc); mixing the RF~Fc with a palladium compound, ball milling, and obtaining a palladium hybrid ferrocene modified phenolic resin, namely the paramagnetic monatomic light self-Fenton catalyst (Pd / RF~Fc). The paramagnetic monatomic light self-Fenton catalyst of the application can be irradiated by visible light, does not need to add H2O2 and Fe 2+ The degradation rate of typical organic pollutants reaches more than 90% within 60 minutes, and the mineralization rate is greater than 70%, which is significantly better than a traditional Fenton system and a single Pd or Fe-based photocatalyst.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of photocatalysis technology, specifically relating to a paramagnetic single-atom photo-self-Fenton catalyst, its preparation method, and its application. Background Technology

[0002] Traditional Fenton technology uses Fe 2+ Catalytic generation of hydroxyl radicals (·OH) from H₂O₂ is the core technology and is widely used in wastewater treatment and organic pollutant degradation, but it has the following problems: (1) Narrow pH range and iron sludge problem: The optimal pH range for the Fenton reaction at the bedside is 2-4. Under neutral or alkaline conditions, Fe(OH)3 precipitate is easily formed, which leads to catalyst deactivation and produces a large amount of difficult-to-treat chemical iron sludge. (2) Strong dependence on H2O2: Additional H2O2 needs to be added, which poses high risks in transportation and storage. Excessive H2O2 will trigger elimination reactions and reduce oxidation efficiency. (3) Slow catalytic cycle: Fe 3+ Reduced to Fe 2+ The rate of reaction is extremely slow, becoming a bottleneck that limits the overall reaction rate.

[0003] To overcome the above problems, researchers have developed a variety of improvement strategies, including heterogeneous Fenton catalysts (such as Fe~MOF, Fe-based zeolites) and Fenton-like systems, which have reduced iron ion loss to some extent. However, they still face problems such as low utilization of active sites, metal leaching under acidic conditions, and large mass transfer resistance. Moreover, most systems still rely on the addition of H2O2.

[0004] Therefore, developing a photo-self-Fenton catalyst with high stability, wide pH applicability, and efficient in-situ H2O2 generation and instantaneous activation capabilities is of great significance for promoting the practical application of advanced oxidation technologies. Summary of the Invention

[0005] This invention provides a paramagnetic single-atom photo-self-Fenton catalyst, its preparation method, and its application, aiming to solve the problem that existing Fenton and photo-Fenton technologies require the addition of H2O2 and Fe. 2+ Overcoming technical challenges such as easy loss, narrow pH range, lack of synergy between H2O2 generation and activation, and difficulty in catalyst recovery, we can achieve efficient, economical, and environmentally friendly degradation of organic pollutants.

[0006] To solve the above-mentioned technical problems, the present invention is implemented as follows: A method for preparing a paramagnetic single-atom photo-self-Fenton catalyst includes the following steps: Step S1: Disperse the ferrocene derivative in an ethanol / water mixed solvent, then add resorcinol to undergo prepolymerization. After the prepolymerization is completed, add formaldehyde solution and catalyst, stir evenly to obtain the precursor solution. Step S2: The precursor solution is transferred to a high-pressure reactor for solvothermal polycondensation reaction. After the reaction is completed, the mixture is cooled to room temperature, the solid product is collected by filtration, and the solid product is dried under vacuum to obtain ferrocene-modified phenolic resin. Step S3: The ferrocene-modified phenolic resin is mixed with a palladium compound and ball-milled to obtain palladium-hybridized ferrocene-modified phenolic resin, which is the paramagnetic single-atom photo-self-Fenton catalyst.

[0007] As a preferred improvement, the ferrocene derivative is one of ferrocene formaldehyde and ferrocene diformaldehyde; the catalyst is one of oxalic acid and acetic acid, and the amount used is 0.1~0.3% of the mass of resorcinol.

[0008] As a preferred improvement, in step S1, the mass ratio of ferrocene derivative to resorcinol is 1:5 to 1:30, and the molar ratio of formaldehyde to resorcinol is 2:1.

[0009] As a preferred improvement, the volume ratio of ethanol to water in the mixed solvent is 1:5 to 1:15.

[0010] As a preferred improvement, in step S2, the temperature of the solvothermal polycondensation reaction is 250°C and the time is 6~24h.

[0011] As a preferred improvement, the palladium compound is either palladium acetate or palladium chloride.

[0012] A paramagnetic single-atom photo-self-Fenton catalyst was prepared using the method described above.

[0013] As a preferred improvement, the mass fraction of Fe in the paramagnetic single-atom photo-self Fenton catalyst is 1~10 wt%, and the mass fraction of Pd is 0.5~3 wt%.

[0014] An application of the paramagnetic single-atom photo-self-Fenton catalyst as described above, used as a photocatalyst for the photocatalytic degradation of organic pollutants.

[0015] As a preferred improvement, the organic pollutants include dyes, antibiotics, phenols, pesticides, and chloroquine phosphate.

[0016] Compared with the prior art, the present invention has the following beneficial effects: (1) Paramagnetism extends charge lifetime: Electron spin channels are constructed by utilizing the electron-donating properties of ferrocene and the π-electron system of RF resin to generate a paramagnetic microenvironment, which slightly perturbs the nearby phenolic hydroxyl groups, lowers the proton dissociation energy barrier, and promotes electron-proton coupling transfer. At the same time, the binding of palladium pairs with the d orbitals and the p orbitals of O accelerates H + The dissociation of O2 increases the efficiency of O2 two-electron reduction to generate H2O2; (2) Bimetallic synergistic photo-self-Fenton mechanism: H2O2 is activated in situ at the Fe center of ferrocene to generate hydroxyl radicals (•OH), and H2O2 is generated at the C=O sites of palladium atoms and RF. The spatial proximity effect at the molecular scale shortens the diffusion path of H2O2, improves the generation efficiency of reactive oxygen species and the efficiency of photo-self-Fenton degradation of organic pollutants. (3) Wide pH adaptability and stability: The covalently anchored Fe center avoids the Fe in the traditional Fenton reaction. 3+ The hydrolysis problem is addressed by the strong metal-carrier interaction of the Pd single atom, which facilitates metal leaching. It maintains high activity within the pH range of 3 to 9, and the activity retention rate is >85% after 5 cycles of use. It has significant application value in wastewater treatment and environmental remediation. Attached Figure Description

[0017] To more clearly illustrate the technical solutions in the embodiments of the present invention, the accompanying drawings used in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort, wherein: Figure 1 SEM image of the paramagnetic single-atom photo-self-Fenton catalyst obtained in Example 2; Figure 2 TEM image showing the paramagnetic single-atom photo-self-Fenton catalyst obtained in Example 2; Figure 3 This diagram shows the long-term H2O2 stability of the paramagnetic single-atom photo-self-Fenton catalyst obtained in Example 2. Figure 4 The graph shows the degradation curve of pollutants by the paramagnetic single-atom photo-self-Fenton catalyst obtained in Example 2. Detailed Implementation

[0018] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0019] like Figures 1-4 As shown, this embodiment provides a method for preparing a paramagnetic single-atom photo-self-Fenton catalyst, comprising the following steps: Step S1: The ferrocene derivative is dispersed in an ethanol / water mixed solvent, and then resorcinol is added to undergo prepolymerization. After the prepolymerization is completed, formaldehyde solution and catalyst are added, and the mixture is stirred evenly to obtain a precursor solution.

[0020] The ferrocene derivative is one of ferrocene formaldehyde and ferrocene diformaldehyde.

[0021] The mass ratio of the ferrocene derivative to resorcinol is 1:5 to 1:30, preferably 1:10 to 1:20, and the molar ratio of formaldehyde to resorcinol is 2:1.

[0022] In the mixed solvent, the volume ratio of ethanol to water is 1:5 to 1:15.

[0023] The catalyst is one of oxalic acid and acetic acid, and the amount used is 0.1~0.3% of the mass of resorcinol.

[0024] The stirring time is 1 to 3 hours.

[0025] In step S2, the precursor solution is transferred to a high-pressure reactor for solvothermal polycondensation. After the reaction is completed, the mixture is cooled to room temperature, the solid product is collected by filtration, and the solid product is dried under vacuum to obtain ferrocene-modified phenolic resin (RF~Fc).

[0026] During the solvothermal polycondensation reaction, the high-pressure reactor is kept sealed, the temperature is maintained at 250℃, and the reaction time is 6~24 h.

[0027] The solid product needs to be washed before drying: it is washed 3 to 5 times with deionized water and ethanol in sequence to remove unreacted monomers and oligomers.

[0028] The drying temperature of the solid product is 60~100℃, and the drying time is 8~24 h.

[0029] Step S3: The ferrocene-modified phenolic resin is mixed with a palladium compound and ball-milled to obtain a palladium-hybridized ferrocene-modified phenolic resin (Pd / RF~Fc), which is the paramagnetic single-atom photo-self-Fenton catalyst.

[0030] The palladium compound is either palladium acetate or palladium chloride.

[0031] The ball milling conditions are: 500 r / min, high-speed ball milling for 20 s.

[0032] The preparation method provided by this invention involves co-condensing a ferrocene derivative (Fc) with resorcinol and formaldehyde. The ferrocene derivative undergoes a co-condensation reaction with resorcinol and formaldehyde via its aldehyde group (-CHO), forming C-C covalent bonds embedded in the phenolic resin (RF) backbone. The ferrocene derivative is randomly distributed in the RF network, forming conjugated and hydrogen-bonded interactions with the aromatic rings and phenolic hydroxyl groups of the RF. Then, palladium single atoms are loaded onto the Fc~RF surface to construct an integrated H2O2 generation-activation photo-self-Fenton system.

[0033] This embodiment also provides a paramagnetic single-atom photo-self-Fenton catalyst, which is prepared using the above-described preparation method.

[0034] The paramagnetic single-atom photocatalyst (Pd / Fc~RF) is composed of Pd single atoms and Fc~RF copolymer resin. The RF framework and Pd sites provide photocatalytic activity and H2O2 generation capability, while the ferrocene units provide Fe. 2+ Active center and electronic regulation function.

[0035] The mass fraction of Fe in the paramagnetic single-atom photo-self-generating Fenton catalyst is 1-10 wt%, preferably 3-7 wt%. If the Fe content is too low, there will be insufficient active sites; if the Fe content is too high, ferrocene may agglomerate, reducing dispersion and activity. The mass fraction of Pd is 0.5-3 wt%.

[0036] The molar ratio of ferrocene units to resorcinol units is 1:5 to 1:30, preferably 1:10 to 1:20. This ratio ensures that the ferrocene units are uniformly dispersed in the RF framework while maintaining the photocatalytic activity of the RF.

[0037] The palladium is loaded in a single-atom manner.

[0038] The paramagnetic single-atom photo-self-Fenton catalyst provided by this invention has the following properties: (1) Electron spin channel construction and proton dissociation promotion Electron-donating effect: The cyclopentadienyl group (Cp) of ferrocene has a strong electron-donating ability, which provides electrons to the π-electron system of RF through the σ~π conjugation effect, increasing the electron cloud density of the RF skeleton; Electron spin channels: Fe in ferrocene 2+ The center has unpaired electrons (d 6 low spin or d 6 High-spin electrons (electrons) couple with the π-electron system of radiofrequency electrons (RF) to form an electron spin channel. This spin channel facilitates the rapid transfer and separation of photogenerated electrons and reduces electron-hole recombination. Paramagnetic microenvironment: The introduction of ferrocene creates a paramagnetic microenvironment. This microenvironment, through the magnetic field-orbit coupling effect, slightly perturbs the OH bonds of neighboring phenolic hydroxyl groups, reducing their bond energy; Enhanced O2 adsorption performance: Pd single atoms enhance the dissociation of adsorbed water protons, providing a sufficient proton source for subsequent electron-proton coupling transfer, and efficiently catalyze the dissolution of O2 to generate H2O2 via 2e-ORR reduction.

[0039] (2) Improved efficiency of in-situ H2O2 generation Enhanced light absorption: The introduction of ferrocene expands the light absorption range of RF, especially the absorption enhancement in the 450~600nm region, which improves the utilization rate of visible light.

[0040] Enhanced charge separation: Electron spin channels facilitate the rapid transfer of photogenerated electrons from the RF framework to ferrocene units or reaction sites, reducing electron-hole recombination and improving quantum efficiency.

[0041] Enhanced oxygen reduction activity: Pd centers can promote the dissociation of adsorbed water to generate H+. + RF~Fc, as active sites for oxygen reduction, promotes O2 adsorption and reduces intermediate products ( The formation energy barrier of OOH.

[0042] H2O2 formation rate: The cumulative H2O2 formation rate of the Pd / Fc~RF catalyst is 1000~3000 μmol·g -1 ·h -1 It is 2 to 6 times that of pure RF.

[0043] (3) In-situ activation of H2O2 and generation of •OH Fenton's active center: Fe in ferrocene 2+ The center possesses Fenton activity and can catalyze the decomposition of H2O2 to produce •OH: H2O2 + Fe 2+ →Fe 3+ +•OH+OH~; In-situ activation: The H2O2 generated in-situ by photocatalysis is then activated into •OH by the Fe centers of ferrocene without needing to diffuse to other sites, thus achieving in-situ generation-activation closed-loop catalysis of H2O2.

[0044] This embodiment also provides an application of a paramagnetic single-atom photo-self-Fenton catalyst, used as a photocatalyst for the photocatalytic degradation of organic pollutants. The paramagnetic single-atom photo-self-Fenton catalyst is dispersed in an aqueous solution containing organic pollutants. Under visible light or sunlight irradiation, the paramagnetic single-atom photo-self-Fenton catalyst generates H2O2 in situ and simultaneously activates to produce •OH, thereby degrading organic pollutants through a photo-self-Fenton reaction.

[0045] Tests showed that, under the conditions of an initial pollutant concentration of 10-200 mg / L in aqueous solution, a reaction temperature of 15-50℃, a pH value of 3-9, a light source wavelength of ≥420 nm, a light intensity of 50-200 mW / cm², a catalyst dosage of 0.1-3.0 g / L, and a reaction time of 1-4 hours, the degradation rate of organic pollutants can reach 85-98%.

[0046] The organic pollutants include dyes (rhodamine B, methylene blue, methyl orange, etc.), antibiotics (tetracycline, norfloxacin, sulfonamides, etc.), phenols (phenol, bisphenol A, etc.), pesticides (atrazine, chlorpyrifos, etc.) and chloroquine phosphate and other recalcitrant organic compounds.

[0047] The degradation principle (photo-self-Fenton method) of organic pollutants by the paramagnetic single-atom photo-self-Fenton catalyst provided by this invention is as follows: (1) By copolymerizing ferrocene into the phenolic resin skeleton, a stable covalent structure is formed, with RF and Pd atoms serving as H2O2 generation sites and Fc serving as Fenton activation centers. (2) The paramagnetic microenvironment generated by ferrocene slightly disturbs the neighboring phenolic hydroxyl groups, lowers the proton dissociation energy barrier, and promotes proton release; (3) Photogenerated electrons undergo electron-proton coupling transfer with protons: O2 + 2H + +2e - →H2O2; (4) The spatial proximity effect at the molecular scale between RF and Pd atoms (generated by H2O2) and Fe centers (activated by H2O2) shortens the diffusion path of H2O2 and increases the generation efficiency of hydroxyl radical •OH: H2O2 + Fe 2+ →Fe 3+ +•OH+OH - ; (5) Fe 3+ Reduced and regenerated into Fe by photogenerated electrons 2+ To achieve catalytic cycling: Fe 3+ +e - →Fe 2+ ; (6) •OH oxidizes and degrades organic pollutants, eventually mineralizing them into CO2 and H2O.

[0048] Compared to traditional Fenton reactions or simple photocatalytic reactions, the photo-self-Fenton method of the present invention has the following advantages: (1) The bimetallic synergistic mechanism of Pd and paramagnetic polymer RF~Fc increases the generation rate of H2O2 in the system, solving the problem of mismatch between the in-situ generation of H2O2 and the instantaneous activation kinetics in the photo-Fenton reaction.

[0049] (2) The yield of H2O2 increased by 2 to 5 times, and the degradation rate increased by 2 to 5 times; (3) Fe covalently intercalates and Pd coordinates, avoiding the metal precipitation and dissolution problems in the traditional Fenton reaction, and broadening the applicable pH range to 3~9, which is superior to the traditional Fenton reaction (pH 2~4). (4) After 5 cycles of use, the activity retention rate is >85%; (5) Visible light driven, high solar energy utilization rate, suitable for practical applications.

[0050] To more clearly illustrate the solution of the present invention, the following comparative experiment was conducted: Example 1 This embodiment provides a method for preparing a paramagnetic single-atom photo-self-Fenton catalyst, comprising the following steps: 0.0174 g of Fc-(CHO)2 was weighed and dispersed in 5 mL of anhydrous ethanol. After ultrasonic dispersion and magnetic stirring for 10 min, a homogeneous solution was formed. Then, 0.40 g of resorcinol and 0.54 mL of oxalic acid solution were added to the solution, and the mixture was stirred continuously at 400 rpm for 2 h to allow the precursor to prepolymerize. Next, 0.56 mL of formaldehyde solution (37 wt%) was slowly added dropwise to the system, and stirring was continued for 2 h to form a pre-crosslinked polymer dispersion. The above mixed solution was transferred to a stainless steel hydrothermal reactor with a polytetrafluoroethylene liner and reacted at 250 °C for 12 h to complete the crosslinking of the polymer. After the reaction, the reactor was allowed to cool naturally to room temperature. The solid product in the reactor was collected by vacuum filtration and washed three times alternately with deionized water and anhydrous ethanol to remove unreacted monomers and oligomers. Finally, the washed product was dried in a vacuum drying oven at 60 °C for 24 h to obtain Fc~RF.

[0051] Example 2 This embodiment provides a method for preparing a paramagnetic single-atom photo-self-Fenton catalyst, comprising the following steps: 0.0174 g of Fc-(CHO) was weighed and dispersed in 5 mL of anhydrous ethanol / water. After ultrasonic dispersion and magnetic stirring for 10 min, a homogeneous solution was formed. Then, 0.40 g of resorcinol and 0.54 mL of oxalic acid solution were added to the solution, and the mixture was stirred continuously at 400 rpm for 2 h to allow prepolymerization of the precursor. Next, 0.56 mL of formaldehyde solution (37 wt%) was slowly added dropwise to the system, and stirring continued for 2 h to form a pre-crosslinked polymer dispersion. The above mixture was transferred to a stainless steel hydrothermal reactor with a polytetrafluoroethylene liner and reacted at 250 °C for 12 h to complete polymer crosslinking. After the reaction, the reactor was allowed to cool naturally to room temperature. The solid product in the reactor was collected by filtration and washed three times alternately with deionized water and anhydrous ethanol to remove unreacted monomers and oligomers. Finally, the washed product was dried in a vacuum drying oven at 60 °C for 24 h to obtain Fc~RF. Weigh 10 mg of Fc~RF into a centrifuge tube, add 0.1 mg / mL palladium chloride, and ball mill for 5 min to obtain the Pd / Fc~RF photo-self-Fenton catalyst.

[0052] The sample obtained in Example 2 was subjected to SEM detection, and the results are as follows: Figure 1 As shown, from Figure 1 It can be seen that the paramagnetic single-atom photo-self-Fenton catalyst has a spherical morphology.

[0053] The sample obtained in Example 2 was subjected to TEM detection, and the results are as follows: Figure 2 As shown, Figure 2 The bright spots are clearly and evenly distributed. The SAED pattern only shows a broad diffuse halo and no long-range ordered crystal diffraction signal was observed, indicating the amorphous structure of the RF~Fc polymer skeleton and also indicating the nanoscale highly dispersed state of the loaded Pd species on the RF~Fc surface.

[0054] Figure 3 This diagram shows the long-term H2O2 stability of the paramagnetic single-atom photo-self-Fenton catalyst obtained in Example 2. Figure 3 It can be seen that the standard deviation of the cumulative H2O2 production rate under continuous 12 hours of light irradiation is 2.5%, indicating that the catalyst has good stability. Figure 4 The graph shows the degradation curves of pollutants by the paramagnetic single-atom photo-self-Fenton catalyst obtained in Example 2. It can be seen from the graph that the degradation performance of pollutants with different structures varies, but the overall degradation efficiency remains above 60%.

[0055] Example 3 This embodiment provides a method for preparing a paramagnetic single-atom photo-self-Fenton catalyst, comprising the following steps: 0.0174 g of Fc-(CHO)2 was weighed and dispersed in 5 mL of anhydrous ethanol. After ultrasonic dispersion and magnetic stirring for 10 min, a homogeneous solution was formed. Then, 0.40 g of resorcinol and 0.54 mL of oxalic acid solution were added to the solution, and the mixture was stirred continuously at 400 rpm for 2 h to allow the precursor to prepolymerize. Next, 0.56 mL of formaldehyde solution (37 wt%) was slowly added dropwise to the system, and stirring was continued for 2 h to form a pre-crosslinked polymer dispersion. The above mixed solution was transferred to a stainless steel hydrothermal reactor with a polytetrafluoroethylene liner and reacted at 250 °C for 24 h to complete the crosslinking of the polymer. After the reaction, the reactor was allowed to cool naturally to room temperature. The solid product in the reactor was collected by vacuum filtration and washed three times alternately with deionized water and anhydrous ethanol to remove unreacted monomers and oligomers. Finally, the washed product was dried in a vacuum drying oven at 60 °C for 24 h to obtain Fc~RF. Weigh 10 mg Fc~RF into a centrifuge tube, add 0.2 mL of 10 mg / mL palladium chloride, and ball mill for 5 min to obtain the Pd / Fc~RF photo-self-Fenton catalyst.

[0056] Example 4 This embodiment provides a method for preparing a single-atom photo-self-Fenton catalyst, comprising the following steps: 0.0174 g of Fc-(CHO)2 was weighed and dispersed in 5 mL of anhydrous ethanol. After ultrasonic dispersion and magnetic stirring for 10 min, a homogeneous solution was formed. Then, 0.40 g of resorcinol and 0.54 mL of oxalic acid solution were added to the solution, and the mixture was stirred continuously at 400 rpm for 2 h to allow the precursor to prepolymerize. Next, 0.56 mL of formaldehyde solution (37 wt%) was slowly added dropwise to the system, and stirring was continued for 2 h to form a pre-crosslinked polymer dispersion. The above mixed solution was transferred to a stainless steel hydrothermal reactor with a polytetrafluoroethylene liner and reacted at 250 °C for 12 h to complete the crosslinking of the polymer. After the reaction, the reactor was allowed to cool naturally to room temperature. The solid product in the reactor was collected by filtration and washed three times alternately with deionized water and anhydrous ethanol to remove unreacted monomers and oligomers. Finally, the washed product was dried in a vacuum drying oven at 60 °C for 24 h to obtain Fc~RF. Weigh 10 mg of Fc~RF into a centrifuge tube, add 0.3 mL of 10 mg / mL palladium chloride, and ball mill for 5 min. Filter and wash to obtain the Pd / Fc~RF photo-self-Fenton catalyst.

[0057] The final samples obtained in Examples 1-4 were subjected to wastewater degradation tests containing chloroquine phosphate. The cumulative H2O2 generation rate, CQ degradation rate, and Pd leaching amount of each sample were obtained, and the results are shown in Table 1. Table 1 Test results of samples 1-4 in Examples As shown in Table 1, the degradation rate of CQ pollutants in this system increases with the increase of the steady-state concentration of H2O2 in the solution. When the Pd content is moderate (loading is 1.2%), the cumulative generation rate of H2O2 is the highest, and its degradation rate of CQ is also the highest. This indicates that the production of H2O2 is a prerequisite and a rate-determining step in the photo-self-Fenton degradation system. It is precisely because of the kinetic matching between H2O2 generation and activation that this system exhibits high pollutant degradation performance.

[0058] The embodiments of the present invention have been described above with reference to the accompanying drawings. However, the present invention is not limited to the specific embodiments described above. The specific embodiments described above are merely illustrative and not restrictive. Those skilled in the art can make many other forms under the guidance of the present invention without departing from the spirit and scope of the claims, and all of these forms are within the protection scope of the present invention.

Claims

1. A method for preparing a paramagnetic single-atom photo-self-Fenton catalyst, characterized in that, Includes the following steps: Step S1: Disperse the ferrocene derivative in an ethanol / water mixed solvent, then add resorcinol to undergo prepolymerization. After the prepolymerization is completed, add formaldehyde solution and catalyst, stir evenly to obtain the precursor solution. Step S2: The precursor solution is transferred to a high-pressure reactor for solvothermal polycondensation reaction. After the reaction is completed, the mixture is cooled to room temperature, the solid product is collected by filtration, and the solid product is dried under vacuum to obtain ferrocene-modified phenolic resin. Step S3: The ferrocene-modified phenolic resin is mixed with a palladium compound and ball-milled to obtain palladium-hybridized ferrocene-modified phenolic resin, which is the paramagnetic single-atom photo-self-Fenton catalyst.

2. The preparation method according to claim 1, characterized in that, The ferrocene derivative is one of ferrocene formaldehyde and ferrocene diformaldehyde; the catalyst is one of oxalic acid and acetic acid, and the amount used is 0.1~0.3% of the mass of resorcinol.

3. The preparation method according to claim 1, characterized in that, In step S1, the mass ratio of ferrocene derivative to resorcinol is 1:5 to 1:30, and the molar ratio of formaldehyde to resorcinol is 2:

1.

4. The preparation method according to claim 1, characterized in that, In the mixed solvent, the volume ratio of ethanol to water is 1:5 to 1:

15.

5. The preparation method according to claim 1, characterized in that, In step S2, the temperature of the solvothermal polycondensation reaction is 250℃, and the time is 6~24h.

6. The preparation method according to claim 1, characterized in that, The palladium compound is either palladium acetate or palladium chloride.

7. A paramagnetic single-atom photo-self-Fenton catalyst, characterized in that, It is prepared by the preparation method described in any one of claims 1 to 6.

8. The paramagnetic single-atom photo-self-Fenton catalyst according to claim 7, characterized in that, The mass fraction of Fe in the paramagnetic single-atom photo-self-Fenton catalyst is 1~10 wt%, and the mass fraction of Pd is 0.5~3 wt%.

9. The application of a paramagnetic single-atom photo-self-Fenton catalyst as described in any one of claims 7-8, characterized in that, Used as a photocatalyst for the photocatalytic degradation of organic pollutants.

10. The application according to claim 9, characterized in that, The organic pollutants include dyes, antibiotics, phenols, pesticides, and chloroquine phosphate.